2002
DOI: 10.1080/10715760290019381
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Prevents Cyclosporine-induced Nephrotoxicity in Isolated and Perfused Rat Kidney

Abstract: Cyclosporine A (CsA) is a potent and effective immunosuppressive agent, but its action is frequently accompanied by severe renal toxicity. The precise mechanism by which CsA causes renal injury is not known. Reactive oxygen species (ROS) have been shown to play a role, since CsA-induced renal lipid peroxidation is attenuated in vivo and in vitro by the concomitant administration of antioxidants such as vitamin E. We show here the effect of the antioxidant melatonin (MLT), a hormone produced by the pineal gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…This result suggests that SP blocks the occurrence of NO and therefore it has a supportive effect on the antioxidant system. Similar antioxidant properties have also been reported in studies using ischaemia re-perfusion injury in the rat brain (Longoni et al, 2002).…”
Section: Discussionsupporting
confidence: 54%
“…This result suggests that SP blocks the occurrence of NO and therefore it has a supportive effect on the antioxidant system. Similar antioxidant properties have also been reported in studies using ischaemia re-perfusion injury in the rat brain (Longoni et al, 2002).…”
Section: Discussionsupporting
confidence: 54%
“…[28,29] Antioxidants such as vitamin E, trimetazidine, melatonin, and n-acetylcysteine have been shown to reduce cyclosporine-induced oxidative stress and prevent renal dysfunction. [8,[29][30][31] In agreement with previous studies, we determined a clear association between renal dysfunction and oxidative stress parameters in cyclosporine treated rats. However, mediators other than reactive oxygen species are also suggested to be involved in cyclosporine nephrotoxicity, including transforming growth factor B1, angiotensin II, nitric oxide, thromboxane A2, and leukotriene.…”
Section: Discussionsupporting
confidence: 90%
“…[4,5] Although many reports suggest that the pathophysiology of GEN-induced nephrotoxicity is unclear, researchers found that in GEN-treated rats, reactive oxygen species (ROS) including superoxide anion (O 2 −• ), [6] hydrogen peroxide (H 2 O 2 ), [7][8][9] and hydroxyl radicals (HO) were found to be enhanced in both in vivo (renal cortex) and in vitro (mitochondrial) models. It was also confirmed by others that ROS participate in all pathological conditions, including glomerular disease, [4] and in renal ischemia and reperfusion injury [10] and other toxic renal failure. [11] In addition, oxidative stress releases iron from mitochondria of renal cortex and forms an iron-GEN complex known as ferrous iron, which is a potent catalyst of free radicals and enhance the generation of ROS.…”
Section: Introductionmentioning
confidence: 50%